2008
DOI: 10.1094/mpmi-21-4-0448
|View full text |Cite
|
Sign up to set email alerts
|

Two Receptor-Like Genes, Vfa1 and Vfa2, Confer Resistance to the Fungal Pathogen Venturia inaequalis Inciting Apple Scab Disease

Abstract: The Vf locus, originating from the crabapple species Malus floribunda 821, confers resistance to five races of the fungal pathogen Venturia inaequalis, the causal agent of apple scab disease. Previously, a cluster of four receptor-like genes, Vfa1, Vfa2, Vfa3, and Vfa4, was identified within the Vf locus. Because the amino-acid sequence of Vfa3 is truncated, it was deemed nonfunctional. In this study, each of the three full-length Vfa genes was introduced into a plant cloning vector, pCAMBIA2301, and used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
54
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 57 publications
1
54
1
1
Order By: Relevance
“…The second largest group of eLRRcontaining cell surface receptors, represented by 57 members in the Arabidopsis genome, is formed by the RLPs, which differ from receptor-like kinases in that they lack a cytoplasmic kinase domain and carry only a short cytoplasmic tail that lacks obvious signaling motifs other than the putative endocytosis motif found in some members Wang et al, 2008). This class of resistance protein was identified originally as Cf resistance proteins that provide resistance in tomato against the foliar leaf mold pathogen Cladosporium fulvum (Jones et al, 1994;Thomma et al, 2005) but also includes the apple (Malus domestica) HcrVf proteins that confer resistance to the scab fungus Venturia inaequalis (Vinatzer et al, 2001;Belfanti et al, 2004;Malnoy et al, 2008). In addition to racespecific resistance proteins, the RLP family harbors receptors that act in basal defense and nonhost resistance, including the tomato LeEIX genes that encode receptors for the ethylene-inducible xylanase produced by Trichoderma biocontrol fungi (Ron and Avni, 2004) and Arabidopsis AtRLP52 and AtRLP30 that provide resistance against the powdery mildew pathogen Erysiphe cichoracearum and nonhost resistance toward Pseudomonas syringae pv phaseolicola, respectively (Ramonell et al, 2005;Wang et al, 2008).…”
mentioning
confidence: 99%
“…The second largest group of eLRRcontaining cell surface receptors, represented by 57 members in the Arabidopsis genome, is formed by the RLPs, which differ from receptor-like kinases in that they lack a cytoplasmic kinase domain and carry only a short cytoplasmic tail that lacks obvious signaling motifs other than the putative endocytosis motif found in some members Wang et al, 2008). This class of resistance protein was identified originally as Cf resistance proteins that provide resistance in tomato against the foliar leaf mold pathogen Cladosporium fulvum (Jones et al, 1994;Thomma et al, 2005) but also includes the apple (Malus domestica) HcrVf proteins that confer resistance to the scab fungus Venturia inaequalis (Vinatzer et al, 2001;Belfanti et al, 2004;Malnoy et al, 2008). In addition to racespecific resistance proteins, the RLP family harbors receptors that act in basal defense and nonhost resistance, including the tomato LeEIX genes that encode receptors for the ethylene-inducible xylanase produced by Trichoderma biocontrol fungi (Ron and Avni, 2004) and Arabidopsis AtRLP52 and AtRLP30 that provide resistance against the powdery mildew pathogen Erysiphe cichoracearum and nonhost resistance toward Pseudomonas syringae pv phaseolicola, respectively (Ramonell et al, 2005;Wang et al, 2008).…”
mentioning
confidence: 99%
“…The first identified RLP gene was tomato (Solanum lycopersicum) Cf-9, a disease resistance gene that mediates resistance against strains of the fungal leaf mold pathogen Cladosporium fulvum that carry the avirulence gene Avr9 (Jones et al, 1994). The RLP disease resistance gene family comprises the tomato Cf and Ve genes that provide resistance against C. fulvum and Verticillium species, respectively, the LeEIX genes that encode receptors for the ethyleneinducible xylanase produced by Trichoderma biocontrol fungi, apple (Malus domestica) HcrVf genes that confer resistance to the scab fungus Venturia inaequalis, and an Arabidopsis (Arabidopsis thaliana) RLP gene (AtRLP52) that provides resistance against the powdery mildew pathogen Erysiphe cichoracearum (Kawchuk et al, 2001;Belfanti et al, 2004;Ron and Avni, 2004;Ramonell et al, 2005;Malnoy et al, 2008;Fradin et al, 2009). Furthermore, we recently demonstrated that Arabidopsis AtRLP30, and possibly AtRLP18, mediates nonhost resistance toward Pseudomonas syringae pv phaseolicola (Wang et al, 2008).…”
mentioning
confidence: 99%
“…4 In addition, it has been found that RLPs are important players in disease resistance. The RLP disease resistance genes include the tomato Cf and Ve genes that provide resistance against Cladosporium fulvum and Verticillium spp., respectively, 5,6 LeEIX genes that combat against the ethylene-inducing xylanase produced from Trichoderma biocontrol fungi, 7 apple HcrVf genes that confer resistance to the scab fungus Venturia inaequalis, 8 the LepR3 and Rlm2 genes that render race-specific resistance to the fungal pathogen Leptosphaeria maculans. 9,10 Genome-wide sequence analyses identified a total of 57 AtRLPs in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%